Preoperative assessment and preparation of patients in the menopausal stage for gynaecological procedures in general anaesthesia - Sobolewski, Bogusław; Woźniak, Piotr; Ziółkowski, Paweł; Stetkiewicz, Tomasz; Oszukowski, Przemysław (Menopause Review/Przegląd Menopauzalny, 2012)
A large number of gynaecological procedures are performed in general anaesthesia. Following the guidelines of modern anaesthesiology enables safe anaesthetization, and as a result – performance of the whole procedure. One of these guidelines is an individualized approach to every patient when preparing her to anaesthetization. For women, the menopause stage is connected not only with deterioration of quality of life, but also with occurrence of chronic illnesses which influence the efficiency of woman’s organism. All that means the necessity of appropriate preparing patients in the menopausal stage to general anaesthesia. Proper preparation makes it possible to achieve a high level of the patient’s and operating team’s security and also translates to a measurable economic effect.